An environmental court in action function, doctrine and process - Preston, Brian J.; Fisher, Elizabeth (LG-21179 Donated by Atty. Antonio A. Oposa, Jr., 2022)
This book provides a critical assessment of the New South Wales Land and Environment Court (NSWLEC). Effective adjudication has become a key consideration for environmental lawyers. One of the most important questions is whether environmental law frameworks need their own courts, with the conclusion being: yes they do. Here, a pioneer of such a court, the NSWLEC is forensically examined to see what it might teach other such courts. Showing a court 'in action' it suggests models that practitioners and policy makers might follow. It also speaks to the environmental law scholars, setting out a conceptual framework for studying such courts as legal institutions"--The Land and Environment Court of New South Wales and the Transnationalisation of Climate Law: The Case of Gloucester Resources v Minister for Planning--Transnational Dimensions of the Land and Environment Court of New South Wales--The International Outreach of the Land and Environment Court of New South Wales: Diffusion in India--Biodiversity and the Land and Environment Court of New South Wales--